Pengelolaan Aset Universitas Gadjah Mada dalam Meningkatkan Kualitas Pelayanan - Maulina Cahyaningrum; Meylina Dhafa Astika Wardhani; Ninik Alawiyah (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2021)
Gadjah Mada University Asset Management is included in the Gadjah Mada University Asset and Environment Management Master Plan. Gadjah Mada University asset management is a campus effort to improve the quality of Gadjah Mada University asset services. Recording of assets from procurement aims to understand the procedures for recording assets and provide recording procedures that are short, correct and accountable. The scope of recording and procuring Gadjah Mada University assets applies to internal agencies and focuses on university property. This study aims to determine how the management of Gadjah Mada University assets such as the provision of campus bicycles, Electrical and Water Installation (ILA), management of roads, buildings and buildings, and management of tombs in the Sawitsari cemetery complex of Gadjah Mada University, as well as waste management services from Gadjah Mada University.